The Effect of Company Growth and Net Profit on Dividend Policy in Coal Mining Subsector Companies Listed on the IDX for the 2022-2024 Period - Arfianty, Arfianty; A. Aminartha Putri, Deasy Soraya (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
The coal mining subsector in Indonesia experienced fluctuations in financial performance during the 2022–2024 period, which affected company profits and dividend policies. This raises questions regarding the influence of company growth and net income on the Dividend Payout Ratio (DPR). This study aims to analyze the effect of company growth and net income on dividend policy in coal mining subsector companies listed on the Indonesia Stock Exchange during 2022–2024. The research employs a quantitative approach using multiple linear regression analysis. Samples were determined through purposive sampling, with secondary data obtained from annual financial reports. The results show that company growth has a significant effect on dividend policy. Similarly, net income also has a significant effect on dividend policy. This study contributes to corporate finance literature by identifying factors influencing dividend policy and provides insights for investors in evaluating dividend sustainability in the coal sector. The research is limited to the coal subsector during the 2022–2024 period and focuses on two main variables. Future research is suggested to include other variables such as liquidity, leverage, and market conditions.